2013
DOI: 10.1161/circulationaha.113.001874
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Acute Myocardial Infarction in HIV-Infected Patients

Abstract: Background— We aimed to assess in-hospital case fatality and 1-year prognosis in HIV-infected patients with acute myocardial infarction. Methods and Results— From the PMSI (Program de Medicalisation des Systèmes d’informatique) database, data from 277 303 consecutive acute myocardial infarction patients hospitalized from January 1, 2005, to December 31, 2009, were analyzed. Surviving patients were followed up for 1 year after discharge. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(62 citation statements)
references
References 36 publications
(53 reference statements)
4
48
2
1
Order By: Relevance
“…However, as the frequency of haemoptysis found in our study correlates with previous studies, we feel that such inaccuracies may not be considerable. Indeed, recent studies that investigated the reliability of PMSI data by comparing them with reference data from other sources, including a stroke registry, a perinatal survey and vaccine safety assessments, showed that PMSI data can be reliably used for epidemiological purposes [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the frequency of haemoptysis found in our study correlates with previous studies, we feel that such inaccuracies may not be considerable. Indeed, recent studies that investigated the reliability of PMSI data by comparing them with reference data from other sources, including a stroke registry, a perinatal survey and vaccine safety assessments, showed that PMSI data can be reliably used for epidemiological purposes [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The French national administrative database, also called the medicalisation of information system programme (PMSI) provides a huge amount of epidemiological information concerning hospitalised French patients [10][11][12][13][14][15][16]. Data pertaining to haemoptysis are reliable enough to count such patients and to describe the aetiologies of the condition.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of PMSI data has already been assessed, 17,18 and PMSI has previously been used to study patients with stroke, myocardial infarction, and AF. [19][20][21] The study population comprised adults with a diagnosis of acute ischemic stroke (I63 and its subsections using International Classification of Diseases, Tenth Revision codes) coded in the principal diagnosis (ie, the health problem that justified admission to hospital), the related diagnosis (ie, potential chronic disease or health state during hospital stay), or the significantly associated diagnosis (ie, comorbidity or associated complication) who were hospitalized from January 1 to December 31, 2009. Of note, asymptomatic cerebrovascular diseases and sequelae of stroke have different codes (I65-I66 and I69 with subdivisions) to be distinguished from acute strokes in the patients of our analysis.…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…Hsue et al 32 reported a higher restenosis rate after PCI in HIV-infected patients than in controls (52% vs. 14%, p=0.006), but other studies 10,11 have reported similar rates of cardiovascular adverse events in patients with and without HIV infection undergoing PCI with drug-eluting stents in the context of ACS.…”
Section: Incidence Of Acute-phase Reinfarction or Restenosis In Hiv Pmentioning
confidence: 97%